BACTERIAL SENSITIVITY TEST KLEBSIELLA SPP. ISOLATED FROM KINTAMANI DOG DIARRHEA AGAINST ANTIBIOTICS - Ananta Kusuma, Anak Agung Gede Agung; Suarjana, I Gusti Ketut; Gelgel, Ketut Tono Pasek (Buletin Veteriner Udayana; Vol. 15 No. 2 April 2023, 2023)
This study aims to determine the pattern of sensitivity of bacteria Klebsiella spp. isolated from kintamani dogs with diarrhea. The sample of this study were 4 isolates of Klebsiella spp. isolated from kintamani dogs with diarrhea. The method used in this study is the Kirby-Bauer disc diffusion method in duplicate using the antibiotics Kanamycin , Sulfamethoxazole-trimethoprim, and Streptomycin . The data obtained were expressed descriptively qualitatively by measuring the antibiotic inhibition zone formed. The results showed that isolates of  Klebsiella spp. 75% intermediate (3 isolates) and 25%(1 isolate) sensitive to Kanamycin , all samples sensitive to Sulfamethoxazole-trimethoprim and 75% (3 isolates) sample intermediate and 25% (1 isolate) sensitive to  Streptomycin .